PERAN PEMEDIASI LOCUS OF CONTROL PADA PENGARUH FINANCIAL KNOWLEDGE DAN FINANCIAL ATTITUDE TERHADAP FINANCIAL MANAGEMENT BEHAVIOR - Bella Cahyaningrum; Muhammad Ali Fikri (Jurnal Ilmu Manajemen, 2021)
This study aims to determine the effect of financial knowledge and financial attitude on financial management behavior with the locus of control as a mediating variable. The population of this study were students of the Faculty of Economics and Business in Yogyakarta, totalling 198.144 respondents. Sampling in this study used the purposive sampling technique by using several criteria. The number of samples in this study was 96 respondents. The method of collecting data is by using a questionnaire. Data analysis tools using SmartPLS version 3.0 software. Scale test results of the instruments used in this study meet the validity and reliability analysis standard. Direct significance testing of the hypothesis shows that financial knowledge has a positive effect on financial management behavior, locus of control mediates the positive effect of financial knowledge on financial management behavior, the financial attitude has a positive effect on financial management behavior, and locus of control mediates the positive effect of financial attitude on financial management behavior.